2021
DOI: 10.46627/sipose.v2i1.57
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19 Pandemic: Higher Education Generation Alpha 5.0

Abstract: no abstract (Guest Editorial)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The study also found the effect of gender on the perceptions of students regarding e-learning but no significant difference in the mean scores was observed. Use of different devices found to be a predictor for the scale utilization of e-learning (Pragholapati, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study also found the effect of gender on the perceptions of students regarding e-learning but no significant difference in the mean scores was observed. Use of different devices found to be a predictor for the scale utilization of e-learning (Pragholapati, 2020).…”
Section: Discussionmentioning
confidence: 99%